Nontyphoidal Salmonella Gastroenteritis in a Tertiary Children’s Hospital in Southern China: Characteristics and Dietary Considerations - Lu Ren; Min Yang; Lanlan Geng; Peiyu Chen; Huan Chen; Sitang Gong; Ding-You Li (Gastroenterology Research and Practice)
Background. Nontyphoidal Salmonella infection is a common cause for acute bacterial gastroenteritis in children in China. There have been no reports of the prevalence of lactose intolerance or food allergies in children with nontyphoidal Salmonella infection. The aim of this study was to characterize nontyphoidal Salmonella gastroenteritis in a tertiary children’s hospital and evaluate clinical presentation, lactose intolerance, and food allergies in children with prolonged nontyphoidal Salmonella gastroenteritis. Methods. A retrospective case-series analysis was carried out in a tertiary children’s hospital in Guangzhou, China. We included all infants and children who were diagnosed with nontyphoidal Salmonella gastroenteritis between 1 January 2014 and 31 December 2016. Patients’ clinical features, feeding patterns, laboratory tests, and treatment outcomes were reviewed. Results. A total of 142 infants and children were diagnosed with nontyphoidal Salmonella gastroenteritis. 52.1% of cases occurred in infants ≤ 12 months of age and the majority (89.4%) in children younger than 3 years old. The most common symptoms were diarrhea (100%), fever (62%), and vomiting (18.3%). Salmonella Typhimurium was the predominant serotype, accounting for 82.4%. 91.5% of patients were treated with antibiotics. Forty-one (28.9%) and 9 (6.3%) children improved with a lactose-free diet and hypoallergenic formula, respectively, when diarrhea persisted for more than a week. Conclusions. Salmonella Typhimurium was the predominant serotype. Most patients with nontyphoidal Salmonella gastroenteritis were younger than 3 years old. Lactose intolerance occurred frequently in children with nontyphoidal Salmonella gastroenteritis and dietary modification should be considered when diarrhea is persistent and prolonged.